HUBUNGAN KEPEMIMPINAN SELF EFFICACY KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA PEGAWAI PADA KANTOR SEKRETARIAT DPRD PROVINSI KALIMANTAN UTARA - Yuni Anita (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
The purpose of this study is to prove and analyze the relationship of leadership and self-efficacy and job characteristics to organizational commitment and performance. The population from this research amounted to 98 respondents. Sample this study is census method, so the sample in this study amounted to 98 respondents. The analysis uses SEM-PLS. The result is leadership positive significant to commitment. Self-efficacy is a positive significant to commitment. Job characteristics positive significant to commitment. Leadership positive significant to performance. Self-efficacy insignificant positive to performance. Positive and insignificant influence job characteristics to performance of the State Civil Apparatus at the DPRD Secretariat Office of North Kalimantan Province.